Canine Vertebral Screw and Rod Fixation System: Design and Mechanical Testing - Lewchalermwong, Pakthorn; Suwanna, Nirut; Meij, Björn P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives To develop the canine vertebral screw and rod fixation system (CVSRF) and to compare the biomechanical properties between CVSRF and the screw and polymethylmethacrylate (Screw-PMMA) technique for internal fixation of the vertebral column in dogs.Methods The CVSRF consisted of vertebral screws with monoaxial side-loaded head, rods and specific inner screws connecting rod to the screw head. The CVSRF prototype was made from titanium alloy and manufactured by the rapid prototype machine. Vertebrectomy models were simulated by ultra-high-molecular-weight polyethylene blocks and tested with the CVSRF system (n = 8) and the Screw-PMMA technique (n = 8). The models were developed according to the American Society for Testing and Materials (ASTM F-1717–04). The biomechanical parameters were the compressive bending yield load, the compressive bending stiffness, the compressive ultimate load and the load displacement curve.Results The mean values of the compressive bending yield load, compressive bending stiffness and compressive ultimate load of the CVSRF were significantly higher than those of the Screw-PMMA technique (p < 0.01). The load displacement curve of the CVSRF showed higher rigidity and durability than that of the Screw-PMMA technique.Clinical Significance This mechanical study indicated that the CVSRF system can be used for canine vertebral stabilization and the biomechanical properties were better than those for the Screw-PMMA device.
Keywords: dog; canine; spine; pedicle screw and rod fixation; vertebral screw